2016
DOI: 10.1007/s00253-016-7494-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity induced by recombinant protein CPSIT_p8 of Chlamydia psittaci

Abstract: Chlamydia psittaci is a zoonotic pathogen with a broad host range that can lead to severe respiratory and systemic disease in humans. Currently, an effective commercial vaccine against C. psittaci infection is not available. The chlamydial plasmid is an important virulence factor and encodes plasmid proteins that play important roles in chlamydial infection and the corresponding immune response. In this study, we assessed the efficacy of vaccination with plasmid proteins at preventing C. psittaci lung infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Our results also show GrpE vaccination in the presence of FCA could induce readily detectable Th1 responses; however, there wasn't increased inflammation in response to the infection or reduced pathological changes of the infected site. FCA are known to enhance the immunogenicity of the immunogen, play an immune regulation role, and increase the immune effect of the antigen, which can modulate immune cells and enhance humoral and cellular immune responses in the host (22,46,47). So we conclude that the GrpE protein in the presence of FCA may induce protective Th1 immune response in mice and be considered as an effective vaccine against U. urealyticum infection.…”
Section: Discussionmentioning
confidence: 70%
“…Our results also show GrpE vaccination in the presence of FCA could induce readily detectable Th1 responses; however, there wasn't increased inflammation in response to the infection or reduced pathological changes of the infected site. FCA are known to enhance the immunogenicity of the immunogen, play an immune regulation role, and increase the immune effect of the antigen, which can modulate immune cells and enhance humoral and cellular immune responses in the host (22,46,47). So we conclude that the GrpE protein in the presence of FCA may induce protective Th1 immune response in mice and be considered as an effective vaccine against U. urealyticum infection.…”
Section: Discussionmentioning
confidence: 70%
“…The lung homogenates were centrifuged (4°C, 15 mins, 6000 rpm) and inoculated on HeLa 229 cell monolayers after being serially diluted of the supernatants determining the C. psittaci titers. Intracellular inclusions of C. psittaci in the lungs were detected by fluorescence microscopy as described previously 7. The lungs from each mouse were embedded in paraffin for a histopathological assay, sectioned and stained with hematoxylin-eosin (H&E) and an UltraSensitive™SP (Rabbit) IHC Kit (Maixin, China) for the evaluation of inflammatory invasion.…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate candidate antigens (Ags) are one of the crucial factors for the development of Chlamydia vaccine 6. There are many studies that have been done to search protective antigens in animal models, such as C. psittaci major outer membrane protein (MOMP) and plasmid-encoded protein 79. Although the protective effects of subunit protein Ags have already been confirmed, the complexity of protection and stability made them far from ideal candidate vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…These trials utilized recombinant proteins (three trials) or plasmids in different vectors (eukaryotic and viral) (two trials). Results from all five studies observed partial protection from infection and/or disease; however, each utilized a different gene or protein making comparisons difficult (Loots et al, 2006; Qiu et al, 2010; Liu et al, 2015; Liang et al, 2016; Ran et al, 2017).…”
Section: Vaccine Trials For Animal Chlamydial Infectionsmentioning
confidence: 99%